2003
DOI: 10.1152/ajpheart.00174.2003
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol inhibits angiotensin II activation of area postrema neurons

Abstract: It is well established that the area postrema, as a circumventricular organ, is susceptible to modulation by circulating hormones and peptides. Furthermore, activation of the area postrema has been shown to modulate central neurons involved in the regulation of cardiovascular function and blood pressure. In particular, the vasoactive peptide angiotensin II (ANG II) has been shown to inhibit baroreflex regulation of heart rate and increase sympathetic outflow and blood pressure via activation of area postrema n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 50 publications
3
25
0
1
Order By: Relevance
“…Studies from our laboratory have shown that 17ß-estradiol facilitates area postrema calciumactivated K + currents and inhibits area postrema neuronal activity (34). 17ß-estradiol also inhibits an increase in (Ca 2+ ) i induced by application of ANG II to cultured area postrema neurons (35). This evidence reinforces the importance of a central antihypertensive action of E2.…”
Section: The Role Of Sex Hormones and Their Central Receptors In Angisupporting
confidence: 58%
“…Studies from our laboratory have shown that 17ß-estradiol facilitates area postrema calciumactivated K + currents and inhibits area postrema neuronal activity (34). 17ß-estradiol also inhibits an increase in (Ca 2+ ) i induced by application of ANG II to cultured area postrema neurons (35). This evidence reinforces the importance of a central antihypertensive action of E2.…”
Section: The Role Of Sex Hormones and Their Central Receptors In Angisupporting
confidence: 58%
“…First, the estrogen profile closely mirrors the pattern of changes in sBRS during the rat estrous cycle (3, 8); a similar direct correlation between the changes in plasma estrogen and baroreflex control of HR has been observed in women during the menstrual cycle (54). Second, numerous studies have demonstrated that estrogen, via an action in the hindbrain, increases BRS (14,23,34,39,47,48). Therefore, we suggest that during proestrus the late afternoon peak in estrogen mediates the increased BRS in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…But, one cannot rule out that the low levels of sex hormones present at this early age could also be involved (45,51). Estradiol pretreatment can affect ANG II-induced changes in intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in cultured area postrema neurons isolated at P10 to P16 (36), although the effect observed in this group of cells is a reduction in the ANG II-induced increase in [Ca 2ϩ ] i . To directly test whether differences in AT 1 receptor-ImG labeling could also be observed at later time points when sex hormones play a greater role, tissue from young adult (4 mo) and middle-aged (12 mo) rats were analyzed.…”
Section: Discussionmentioning
confidence: 99%